Oral fructose absorption in obese children with non‐alcoholic fatty liver disease. Issue 3 (24th June 2014) - Sullivan, J. S.; Le, M. T.; Pan, Z.; Rivard, C.; Love‐Osborne, K.; Robbins, K.; Johnson, R. J.; Sokol, R. J.; Sundaram, S. S.
Abstract Background Fructose intake is associated with non‐alcoholic fatty liver disease (NAFLD) development. Objective The objective of this study was to measure fructose absorption/metabolism in paediatric NAFLD compared with obese and lean controls. Methods Children with histologically proven NAFLD, and obese and lean controls received oral fructose (1 g kg−1 ideal body weight). Serum glucose, insulin, uric acid, and fructose, urine uric acid, urine fructose, and breath hydrogen levels were measured at baseline and multiple points until 360 min after fructose ingestion. Results Nine NAFLD (89% Hispanic, mean age 14.3 years, mean body mass index [BMI] 35.3 kg m−2), six obese controls (67% Hispanic, mean age 12.7 years, mean BMI 31.0 kg m−2) and nine lean controls (44% Hispanic, mean age 14.3 years, mean BMI 19.4 kg m−2) were enrolled. Following fructose ingestion, NAFLD vs. lean controls had elevated serum glucose, insulin and uric acid (P < 0.05), higher urine uric acid (P = 0.001), but lower fructose excretion (P = 0.002) and lower breath hydrogen 180‐min AUC (P = 0.04). NAFLD vs. obese controls had similar post‐fructose serum glucose, insulin, urine uric acid and breath hydrogen, but elevated serum uric acid (P < 0.05) and lower urine fructose excretion (P = 0.02). Conclusions Children with NAFLD absorb and metabolize fructose more effectively than lean subjects, associated with an exacerbated metabolic profile following fructose ingestion.